2021
DOI: 10.1016/j.jcv.2021.104933
|View full text |Cite
|
Sign up to set email alerts
|

Stability of SARS-CoV-2 IgG in multiple laboratory conditions and blood sample types

Abstract: BACKGROUND : COVID-19 seroprevalence studies use serum/plasma samples to detect SARS-CoV-2 IgG. Data supporting alternate specimen types and freeze-thaw antibody stability is lacking. The stability of IgG and other immunoglobulins in multiple blood sample types stored in differing conditions and multiple freeze-thaw cycles (FTCs) was evaluated. MATERIALS AND METHODS : Serum, plasma, and heparinized-plasma samples were collected from COVID-19 recovered individuals. Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…This finding might be caused either by increased MOG-IgM having initially resulted in falsely positive MOG-IgG titres in assays using H + L-specific rather than Fc(gamma)-specific detection antibodies, 28 , 41 by isolated CSF MOG-IgG but negative serum MOG-IgG positivity, 43 , 44 by immunosuppressive treatments, 6 , 23 the timing of sample collection in regard to the neurological presentation 45 , 46 or by the degradation of antibodies due to repeated freeze-thaw cycles. 47 , 48 This is important because the purification of antigen-specific antibodies is dependent on antibody titre and consequently was less efficient in samples with lower antibody levels to MOG or SARS-CoV-2 S and N proteins. However, only few (15%) of the included patients were on suppressive treatment at sampling with comparable frequencies in all groups ( Table 1 ) and most samples (71%) were obtained within 3 months after the neurological event.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be caused either by increased MOG-IgM having initially resulted in falsely positive MOG-IgG titres in assays using H + L-specific rather than Fc(gamma)-specific detection antibodies, 28 , 41 by isolated CSF MOG-IgG but negative serum MOG-IgG positivity, 43 , 44 by immunosuppressive treatments, 6 , 23 the timing of sample collection in regard to the neurological presentation 45 , 46 or by the degradation of antibodies due to repeated freeze-thaw cycles. 47 , 48 This is important because the purification of antigen-specific antibodies is dependent on antibody titre and consequently was less efficient in samples with lower antibody levels to MOG or SARS-CoV-2 S and N proteins. However, only few (15%) of the included patients were on suppressive treatment at sampling with comparable frequencies in all groups ( Table 1 ) and most samples (71%) were obtained within 3 months after the neurological event.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated antibody activity or titer after freeze-thaw cycles, and most of the results described that antibody activity or titer were preserved after the freeze-thaw process [10] , [15] . Plasma antibodies against SARS-CoV-2 collected from convalescent participants were also evaluated after the freeze-thaw cycle, and the activities did not change significantly [16] . However, to the best of our knowledge, there are no studies evaluating convalescent plasma products manufactured for clinical usage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the storage of the serum sample at −20 °C before testing might also contribute the lower antibody responses observed in our study, although previous studies have demonstrated that multiple freeze--thaw cycles had no effect on the ability of the ELISA assay to detect SARS-CoV-2 IgG antibodies. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%